2016
DOI: 10.1088/1751-8113/49/26/265203
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of compact laser pulses

Abstract: We discuss the use of a class of exact finite energy solutions to the vacuum source-free Maxwell equations as models for multi-and single cycle laser pulses in classical interaction with relativistic charged point particles. These compact solutions are classified in terms of their chiral content and their influence on particular charge configurations in space. The results of such classical interactions motivate a phenomenological quantum description of a propagating laser pulse in a medium in terms of an effec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…A choice of values for the dimensionless parameters { 0 , a, b, q, m 0 } can be used to solve (23) numerically for a collection of trajectories for charged particles, each arranged initially around the circumference of a circle in a plane orthogonal to the propagation axis of incident CM type electromagnetic pulses with different chirality. The resulting space-curves in 3-dimensions, displayed in figure 1 clearly exhibit the different responses of charged matter to CM pulses with distinct chirality values [10]. Similar space-curves arise from charged particles interacting with chiral CE type modes.…”
Section: Electromagnetic Pulses In Spacetime Vacuamentioning
confidence: 86%
See 1 more Smart Citation
“…A choice of values for the dimensionless parameters { 0 , a, b, q, m 0 } can be used to solve (23) numerically for a collection of trajectories for charged particles, each arranged initially around the circumference of a circle in a plane orthogonal to the propagation axis of incident CM type electromagnetic pulses with different chirality. The resulting space-curves in 3-dimensions, displayed in figure 1 clearly exhibit the different responses of charged matter to CM pulses with distinct chirality values [10]. Similar space-curves arise from charged particles interacting with chiral CE type modes.…”
Section: Electromagnetic Pulses In Spacetime Vacuamentioning
confidence: 86%
“…More generally, the classical configurations of a high energy pulse labelled CE or CM could be distinguished experimentally by its interaction with different arrangements of charged matter. Particular choices of pulse parameters { 0 , a, b} can be made to model the physical characteristics of existing laser pulses and have been used, for electromagnetic micropulses of duration t 0 with Et 0 , to model an effective description of general non-stationary quantum states of a laser pulse [10]. It is suggested that such a description may have utility for simulating a novel transfer of quantum information and may be worthy of further investigation for technological applications such as quantum computing and encryption.…”
Section: Electromagnetic Pulses In Spacetime Vacuamentioning
confidence: 99%
“…A choice of dimensionless parameters can be used to solve (4) numerically for a collection of trajectories for charged particles, each arranged initially around the circumference of a circle in a plane orthogonal to the propagation axis of incident CM type electromagnetic pulses with different chirality. The resulting space-curves in 3-dimensions, displayed in figure 1, clearly exhibit the different responses of charged matter to CM pulses with distinct chirality values [16]. Similar space-curves arise from charged particle interacting with chiral CE type modes .…”
Section: Electromagnetic Pulses In Vacuamentioning
confidence: 86%
“…In particular, we construct families of plane-fronted gravitational wave metrics and new non-stationary metrics having propagating pulse-like characteristics with bounded components in three-dimensional spatial domains. These are analogous to particular exact solutions of the vacuum Maxwell equations which we have recently shown can be used to model single-cycle electromagnetic laser pulses [11,12].…”
Section: Introductionmentioning
confidence: 82%